Effects of a local aphrodisiac on body weight changes, LD50, lipid profile, liver enzymes and antioxidant activities of male Wistar rats (African Journal of Biomedical Research, 2024)
Rejuvenator is a local commercial libido enhancing drink extensively consumed in Nigeria as ‘over-the-counter product’. Following reports from the users, it is alleged to improve libido and fertility in males. Listed as ingredients are Tribulus terrestris, Capsasine, Cilantrosied, Myristica fragrans, Zingiber officinale, Rhodiola rosea, Ocinum bacilicum, honey and cinnamon, which are natural products believed to treat erectile dysfunction in males and other ailments. In this study we aimed at investigating the effect of this aphrodisiac on LD50, body weight changes and some other biochemical parameters to ascertain the implications if any of the drink on the living system. In the experimentation, fractions of the drink (100, 200 and 400 mg/kg bodyweight) and Viagra (100 mg/kg bodyweight) were administered to Wistar rats for 21 days. Toxicity evaluation of the drink revealed that its LD50 is above 5000 mg/kg body weight. A favorable lipid profile was observed in the test groups and no significant negative impact was seen on the antioxidant enzymes. The drink has the tendency of increasing body weight and may impact the liver as both ALT and ALP were significantly high (p < 0.05) in group 3. The study has revealed that the drink has no toxicity challenge (LD50 > 5000 mg/kg bw) nor the tendency to increase free radical activity in the system as well as triggering lipid peroxidation. The animals possessed favorable lipid profile, though; some liver enzymes increased which suggests that the drink could impact on the liver and may be greater after a long-term use. Finally, the drink has the tendency to increase weight